Quo vadis, Schuldenbremse? Über Sinn und Unsinn detaillierter Defizit- und Schuldenregelungen im Grundgesetz - Dirk Ehnts (Wirtschaftsdienst, 2024)
– The German debt brake forces the German government to target a very specific public deficit to GDP ratio. A ruling of the German constitutional court has drawn attention to the debt brake, as it is to be enforced more tightly than the federal German government previously thought. In this article, the author argues that the debt brake should be abolished. It does not do what it is supposed to do - the sustainability of public debt depends on the European Central Bank's Dealer of Last Resort function and nothing else. As a side effect, the debt brake curtails government spending at a time of close to zero net public investment and huge requirements for more public spending.
Keywords: H60; E62; 330; Öffentliche Schulden; Deutschland; Öffentliche Schulden; Deutschland